Huawei and the Gulf Region: Market Opportunities Despite the Ongoing US-China Trade War - Alfayad, Fadye Saud (International Review of Management and Marketing, 2019)
This document discusses the Chinese telecommunications firm Huawei and its market opportunities in the Gulf Cooperation Council (GCC) are discussed in comparison to the recent sanctions taken against the firm by the US government and the ongoing US-China trade war. The analysis first offers some background information of the US-China trade war that has been rattling the global financial markets for months. This is followed by the examination of the sanctions taken against Huawei by the US government and the reasons for them. Into this milieu, potential market opportunities for Huawei are explored within the GCC and especially its leading member-state markets such as Saudi Arabia. The observation is made that despite the US sanctions, Huawei is certainly the leading telecommunications equipment provider internationally. These attributes of the firm's business case provide it with the commercial heft necessary in order to convince the GCC and its member-states that it is a safe harbor investment for their 5G network build-out. The recommendation is made that Huawei make price concessions to the GCC and its member states in order to convince them to offer exclusive 5G vendor contracts. This exclusivity in the market would stabilize Huawei's revenues over the long-term. Keywords: GCC Market, US-China Trade War, 5G Technologies JEL Classifications: M3, O3 DOI: https://doi.org/10.32479/irmm.8206